Withholds to Slow Medicare Spending: A Better Deal Than Cuts - Skinner, Jonathan S.; Weinstein, James; Fisher, Elliott S. (JAMA, 2012)
Consensus has emerged on the need to slow Medicare spending growth, but there is no agreement on how best to do so. Although many approaches have been suggested, Congress is almost certain to consider across-the-board cuts in reimbursement rates. It is not hard to understand why: cuts are easy to implement and appear to deliver clear savings. But cuts in fees are a poor long-term solution to the problem of increasing health care costs. They make it more likely that physicians will decide not to accept new Medicare patients; further penalize already efficient systems; cause some to increase utilization to make up for revenue losses; and—most importantly—do little to encourage the collaborative efforts needed to improve health, better coordinate care, reduce regional duplication, and help beneficiaries avoid unnecessary care.